Inclusion of Ukrainian children and youth in the polish educational system as an element of social security for students with refugee experience - Lubimow Joanna (2022)
The considerations undertaken in the article cover the issue of tools for including children with refugee experience from Ukraine in the school environment as an apparatus affecting the state of social security and being one of the determinants of the state's ability to ensure social security. It was assumed that the aim of the study will be to characterize the processes of support in Polish schools in the field of integration of refugee students with the Polish education system. The following hypothesis was adopted:the practice of using the integration tools formulated in the law showed the imperfection of the created system of support for foreign students in the integration process. In the article there is used research conducted as part of the project "Inclusion processes of immigrants of Ukrainian origin in Polish society on the example of the Lubuskie Voivodeship" implemented as part of the Public Diplomacy 2022 competition. The research process was conducted using the formal-dogmatic method, the methods of analysis and criticism of the literature, methods of quantitative research and qual-itative research. Quantitative and qualitative research was conducted from 6 to 24 June 2022 in schools attended by children from Ukraine living in Gorzów Wielkopolski. The general conclusion regarding the conducted considerations is that the system of supporting the inte-gration of students with refugee experience requires verification in terms of normative, infrastructural and personnel solutions.